2002
DOI: 10.1017/s0952836902000705
|View full text |Cite
|
Sign up to set email alerts
|

Movements of whale sharks (Rhincodon typus) in South‐east Asian waters as determined by satellite telemetry

Abstract: Management of whale shark Rhincodon typus populations is hampered by a lack of information on the range travelled by individual whale sharks. This applies particularly in South-east Asia where the whale shark is increasingly used in commercial trade and for ecotourism. In this study an investigation of the movements of individual whale sharks from the greater Sulu Sea region was initiated using satellite telemetry. The movements of six sharks were monitored from 7 to 128 days. Two sharks travelled distances of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 6 publications
5
68
0
Order By: Relevance
“…data). In Indonesia, sharks are a major target of artisanal and commercial fisheries and it is likely that whale sharks are hunted in these waters as is the case in much of Southeast Asia (Eckert et al 2002). If over-fishing is occurring in part of the range of the Ningaloo sharks, the observation that many individuals return to this aggregation suggests that any demographic effects of this process will be seen in the protected population at Ningaloo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…data). In Indonesia, sharks are a major target of artisanal and commercial fisheries and it is likely that whale sharks are hunted in these waters as is the case in much of Southeast Asia (Eckert et al 2002). If over-fishing is occurring in part of the range of the Ningaloo sharks, the observation that many individuals return to this aggregation suggests that any demographic effects of this process will be seen in the protected population at Ningaloo.…”
Section: Discussionmentioning
confidence: 99%
“…If these estimates are correct, population reduction due to over fishing is likely and recovery will be slow. Additionally, recent studies have shown that the species is highly migratory, with some individuals travelling thousands of kilometres across oceans (Eckert et al 2002). The effects of over fishing in one part of the species range may thus be manifested in populations at other localities where the animals are protected from exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Bruce et al 2006) to transoceanic (e.g. Eckert & Stewart 2001, Eckert et al 2002, Gore et al 2008) and trans-equatorial (e.g. Skomal et al 2009) crossings.…”
Section: Migrationsmentioning
confidence: 99%
“…Tracking studies and mtDNA data indicate, however, that whale sharks may be highly mobile between these visits (e.g. Eckert & Stewart 2001, Eckert et al 2002, Castro et al 2007, Hsu et al 2007, Rowat & Gore 2007, Brunnschweiler et al 2009), suggesting that multilateral regional cooperation and marine resource governance may be the key to conservation of whale sharks (Castro et al 2007).…”
Section: Introductionmentioning
confidence: 99%